Dialogic Learning Environments That Enhance Instrumental Learning and Inclusion of Students With Special Needs in Secondary Education - Navarro-Mateu, Diego; Gómez-Domínguez, Teresa; Padrós Cuxart, María; Roca-Campos, Esther (Frontiers in Psychology, 2021)
Across Europe, the enrolment of students with special educational needs in regular classrooms is increasing, although it does not always mean access to high quality educational experience. In this context, inclusive education has been enhanced in most educational systems, but its successful implementation is still limited and has become a challenge in most countries, and specially in secondary education, when segregation due to learning achievement is more frequent. Educational practices that take into account the potential of promoting learning interactions within heterogeneous groups of students have already demonstrated contributing to educational inclusion of students with special needs. In this study we analyse the case of a secondary education school located in Valencian Community (Spain), which educates students with special needs along with their typically developing peers and is characterised by its inclusive ethos. The analysis focuses on three educational strategies implemented in the school and their impact on educational improvement and inclusion of the students with special needs: (1) co-teaching, (2) interactive groups, (3) dialogic literary gatherings. Qualitative data were obtained from communicative focus groups with teachers, communicative life stories with students and relatives, communicative observations of the three educational strategies and documentary analysis. The results show significant increase in the students’ instrumental learning, as well as an improvement in these students’ overall inclusion in the school.